Conception et validation d’un modèle d’analyse et de suivi pour l’élaboration d’une politique énergétique durable et acceptable : une étude comparative France-Québec sur l’énergie éolienne - Évariste Feurtey; Carol Saucier; Adrian Ilinca; Anas Sakout (VertigO)
This article presents the main results of a doctoral thesis which analyze the various components involved in the development of a sustainable and socially acceptable energy policy for wind energy through a comparative study of France and Quebec. A conceptual model has been developed and validated by a qualitative methodology; it serves to illustrate the interactions between variables, including national context of emergence, balance of power between pressure groups, supranational and exogenous influences, level of political commitment, policy and regulatory instruments, social acceptance and energy policy assessment. The research confirms that the initial unfavorable energy context and the neocorporatism limited the place given to wind energy in both national jurisdictions. These factors have delayed the development of projects and industrial sector influencing negatively the level of political will for this type of energy. This unstable political commitment did not consolidate the 1990’s opportunity window for wind energy, because of social acceptance issues related to a criticism of a too private and expensive development model, lack of initial planning , a too centralized and not enough participatory planning system, and the lack of space in France or the electricity surplus combining with low exporting electricity costs in Quebec. In recent years, the pace of development slowed due to a lack of continuity of call for tenders (CT) in Quebec, and to a too complex and unstable regulatory framework which counterbalanced the positive effect of feed-in tariffs (FIT) in France. The level of political commitment toward wind energy can be measured by the level and stability of financial and regulatory instruments, which are two key elements of the diffusion process of projects or technology: They must be both simultaneously adequate and stable in the medium term in order to reach a sufficient market size in volume, able to catalyze the development of a domestic industrial sector. This was not the case in these two jurisdictions. A wind energy policy will be more socially accepted in the future if: 1) the wind energy field is relevant in the national energy mix. Its place should be more consensual and its development should not lead to excessive costs to society; 2) project ownership are mostly accepted; 3) the projects are locally accepted. This finding confirms the results of Jegen and Audet (2011): a hybrid model of development based on a diversity of ownerships, size of projects and pricing mechanisms (CT and FIT) would be an acceptable compromise able to achieve this balance. The research adds that that there is also a need to improve the way in which projects or energy policies are evaluated, because citizens should have a more direct effect on their development prior to their implementation. This calls for an ecological modernization of institutions, notably based on more open and participatory process.